1970
DOI: 10.54155/jbs.26.1.119-140
|View full text |Cite
|
Sign up to set email alerts
|

Remittances and The Household's Expenditures On Health

Abstract: This paper considers the effect of remittances on the share of health expendituresin total household expenditure in Mexico. The main purpose of this paperis to investigate if remittances are especially targeted towards household's healthexpenditure in Mexico. Using IV Tobit and regression models we find a statisticallysignificant effect of remittances on the household health expenditures shares. Thiseffect is even more pronounced for households without access to the employment'smedical insurance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 1 publication
1
5
0
2
Order By: Relevance
“…Contrary to this, there are a few studies observing limited influence of remittances on education investment (Airola, 2007;Cattaneo, 2010). Remittances are found to have significant effects on expenditures on health in the developing world (Cardona Sosa & Medina, 2006;Catalina & Pozo, 2011;Valero-Gil, 2009), where most medical care is still paid from out-of-pocket. Thus, in general, majority of the studies support the fact that remittances not only increase the incomes of the households that receive the funds, they also serve to enrich the human and social capital of origin households.…”
Section: Remittances and Household Development: Theory And Evidencementioning
confidence: 98%
“…Contrary to this, there are a few studies observing limited influence of remittances on education investment (Airola, 2007;Cattaneo, 2010). Remittances are found to have significant effects on expenditures on health in the developing world (Cardona Sosa & Medina, 2006;Catalina & Pozo, 2011;Valero-Gil, 2009), where most medical care is still paid from out-of-pocket. Thus, in general, majority of the studies support the fact that remittances not only increase the incomes of the households that receive the funds, they also serve to enrich the human and social capital of origin households.…”
Section: Remittances and Household Development: Theory And Evidencementioning
confidence: 98%
“…There are other channels through which remittances could affect growth, namely human capital and labor supply. Thus, remittances can stimulate investment in human capital and health as well (Mansuri 2006, Valero-Gil 2008. They may also influence economic growth via their effects on the labor force participation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Smith (1776) defined human capital as skills gained through experience, education, and training, which contribute to societal value. Valdero Gil (1970) found that remittances have a significant positive effect on health outcomes in Mexico, particularly for households without health insurance. Anten (2010) discovered that remittances have a substantial beneficial effect on the nutritional status of Ecuadorian children.…”
Section: Literature Reviewmentioning
confidence: 99%